Dough properties and baking quality of near isogenic lines with single HMW-GS null at Glu-A1, Glu-B1 and Glu-D1 loci in soft wheat - Pingping Zhang; Guicheng Song; Ibba, Maria Itria; Huadun Wang; Runsheng Ren (Elsevier, 2024)
High molecular weight glutenin subunits (HMW-GSs) encoded by the Glu-1 loci are key factors in determining wheat processing quality. However, the contributions of single HMW-GS to dough viscoelastic properties and end-use quality have not been well understood, especially in soft wheat. In this study, the kernel samples of five Near Isogenic Lines (NILs) of a soft wheat each with individual HMW-GS null were investigated. Significant lower SDS-sedimentation volume and lactic acid solvent retention capacity (SRC) were observed in the NILs, compared to the wild type (WT). Except for the NIL with Glu-D1y12 null, the other NILs were associated with significantly lower dough mixing tolerance compared to the WT. Also, the deletion of individual HMW-GS was associated with reduction in dough elasticity and strength, compared to the WT, with the exception of the Glu-A1x1 null. Moreover, Glu-B1x7 was the most important HMW-GS in determining dough mixing tolerance and elasticity. Compared to the WT, the deletions of Glu-D1x2, Glu-B1x7 and Glu-B1y8 significantly increased alveograph L, and decreased alveograph P and P/L ratios. All NILs with single HMW-GS null showed better sugar snap cookie baking quality than the WT. New germplasm and tools are identified for improving dough viscoelasticity and baking quality in soft wheat.